Rapid and easy method for monitoring oxidative stress markers in body fluids of patients with asbestos or silica-induced lung diseases - Syslová, Kamila; Kacer, Petr; Kuzma, Marek; Najmanová, Vera; Fenclová, Zdenka; Vlcková, Stepánka; Lebedová, Jindriska; Pelclová, Daniela (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2009)
Sensitive assay method was developed for a parallel, rapid and precise determination of the most prominent oxidative stress biomarkers: 8-iso-prostaglandin F(2alpha), malondialdehyde and 4-hydroxynonenal. The method consisted of a pre-treatment part a solid-phase extraction, for rapid and effective isolation of biomarkers from body fluids (exhaled breath condensate, plasma and urine) and the detection method LC-ESI-MS/MS, where the selected reaction monitoring mode was used for its extremely high degree of selectivity and the stable-isotope-dilution assay for its high precision of quantification. The developed method was characterized by the following parameters: the imprecision was below 14.3%, the mean inaccuracy was determined to be lower than 13.1%. The method was tested on samples obtained from patients diagnosed with asbestosis, pleural hyalinosis or silicosis, i.e. occupational lung diseases caused by fibrogenic dusts, inducing oxidative stress in the respiratory system, and then compared to samples from healthy subjects. The difference in concentration levels of biomarkers between the two groups was perceptible in all the body fluids (the difference observed in an exhaled breath condensate was statistically most significant).
Keywords: senioři; oxid křemičitý; azbest; Malondialdehyde; Aldehydes; malondialdehyd; plicní nemoci; dinoprost; Middle Aged; Dinoprost; studie případů a kontrol; Chromatography, High Pressure Liquid; Oxidative Stress; Body Fluids; vysokoúčinná kapalinová chromatografie; tělesné tekutiny; extrakce na pevné fázi; Solid Phase Extraction; Lung Diseases; Humans; Silicon Dioxide; Tandem Mass Spectrometry; biologické markery; Asbestos; lidé středního věku; tandemová hmotnostní spektrometrie; oxidační stres; Biomarkers; Aged; lidé; Case-Control Studies; aldehydy